Pathological Changes and Cause of Death Associated with the Global Novel Coronavirus Disease （COVID-19） - Bin YANG, Lu-yao XU, Ling-yue LI, Dong-fang QIAO, Si-hao DU, Xia YUE, Hui-jun WANG (Fayixue Zazhi, 2023)
The coronavirus disease 2019 （COVID-19） has been a global epidemic for more than three years, causing more than 6.9 million deaths. COVID-19 has the clinical characteristics of strong infectivity and long incubation period, and can cause multi-system damage, mainly lung damage, clinical symptoms of acute respiratory distress syndrome （ARDS） and systemic multiple organ damage. The SARS-CoV-2 virus is still constantly mutating. At present, there is no global consensus on the pathological changes of COVID-19 associated deaths and even no consensus on the criteria for determining the cause of death. The investigation of the basic pathological changes and progression of the disease is helpful to guide the clinical treatment and the development of therapeutic drugs. This paper reviews the autopsy reports and related literature published worldwide from February 2020 to June 2023, with a clear number of autopsy cases and corresponding pathological changes of vital organs as the inclusion criteria. A total of 1 111 autopsy cases from 65 papers in 18 countries are included. Pathological manifestations and causes of death are classified and statistically analyzed, common pathological changes of COVID-19 are summarized, and analytical conclusions are drawn, suggesting that COVID-19 infection can cause life-threatening pathological changes in vital organs. On the basis of different health levels of infected groups, the direct cause of death is mainly severe lung damage and secondary systemic multiple organ failure.